Mindful parenting : - Bögels, Susan M. (Mindfulness in behavioral health,, 2014)
Despite its inherent joys, the challenges of parenting can produce considerable stress. These challenges multiply and the quality of parenting suffers when a parent or child has mental health issues, or when parents are in conflict. Even under optimal circumstances, the constant changes as children develop can tax parents' inner resources, often undoing the best intentions and parenting courses. Mindful Parenting: A Guide for Mental Health Practitioners offers an evidence-based, eight week structured mindfulness training program for parents with lasting benefits for parents and their children. Designed for use in mental health contexts, its methods are effective whether parents or children have behavioral or emotional issues. The program's eight sessions focus on mindfulness-oriented skills for parents, such as responding to (as opposed to reacting to) parenting stress, handling conflict with children or partners, fostering empathy, and setting limits. The book dovetails with other clinical mindfulness approaches, and is written clearly and accessibly so that professionals can learn the material easily and impart it to clients. Featured in the text: Detailed theoretical, clinical, and empirical foundations of the program. The complete Mindful Parenting manual with guidelines for eight sessions and a follow-up. Handouts and assignments for each session. Findings from clinical trials of the Mindful Parenting program. Perspectives from parents who have finished the course. Its clinical focus and empirical support make Mindful Parenting an invaluable tool for practitioners and clinicians in child, school, and family psychology, psychotherapy/counseling, psychiatry, social work, and developmental psychology.